2021
DOI: 10.1177/09685332211020786
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-counter sales of antibiotics for human use in India: The challenges and opportunities for regulation

Abstract: This article assesses the regulatory framework relating to over-the-counter (OTC) sales of antibiotics for human use in India. The OTC sale of antibiotics is recognised as a pathway for the emergence of antimicrobial resistance (AMR); a serious public health challenge in need of urgent regulatory responses. Analytically, this article identifies opportunities within existing laws in India and highlights gaps that need to be filled by modifying existing laws or developing new ones. Conceptually, it suggests a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Antibiotics are prescription only medications for humans and animals in the three countries, with the exception of veterinary antibiotics ‘when contained in preparations for animal feeding stuffs’ in Uganda, which are allowed to be sold OTC [ 44 , 45 , 46 , 47 ]. However, in all three countries, veterinary and human antibiotics are frequently acquired OTC [ 38 , 40 , 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotics are prescription only medications for humans and animals in the three countries, with the exception of veterinary antibiotics ‘when contained in preparations for animal feeding stuffs’ in Uganda, which are allowed to be sold OTC [ 44 , 45 , 46 , 47 ]. However, in all three countries, veterinary and human antibiotics are frequently acquired OTC [ 38 , 40 , 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Customers’ reasons to obtain antibiotics are the belief that antibiotics can speed up recovery and many keep leftover antibiotics for future use [ 46 ]. Losing income and clients has been a concern as commercial pressures drive overprescribed antibiotics [ 65 , 66 ]. In this research, some community pharmacists suggested that a substitutional strategy could compensate their income if they decrease antibiotic sales by rational antibiotic dispensing.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed at recruiting the part- and full-time registered practicing community pharmacists from all regions of Thailand. Based on the 2020 census, the population of Thailand was approximately 70 million and active social media users were 52.63 million [ 66 , 68 ]. The survey link and recruitment advertisement in social media (FacebookTM and LineTM) were shared with almost 13,906 community pharmacies across 77 provinces [ 72 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, rather than placing the onus on individuals and individual institutions to fix the holes in a complex regulatory system, at a higher level we note that regulatory policy itself could be changed so that it is more responsive to on-the-ground implementation. Scholars working in India, for example, have recommended adopting a broader concept of regulation and enhancing the participation of key stakeholders in regulatory design to address similar issues of regulatory complexity ( Porter et al , 2021 ).…”
Section: Discussionmentioning
confidence: 99%